TERAPI AKTIVITAS KELOMPOK TERHADAP KUALITAS HIDUP PENGARUH LANSIA - Juliandi; Cecep Tribowo (Poltekkes Kemenkes Medan, 2021)
Group therapy is a method of treatment that is carried out when a patient is met in a certain time frame with personnel who meet certain requirements. The quality of life is closely related to the environment where the elderly live. The elderly generally live with their families, but not a few elderly people live in nursing homes. There is a significant difference in the quality of life of the elderly in the UPT Social Services for the elderly and children under five in Binjai area between before and after giving group activity therapy in the intervention group with a p value of 0.008.There was no significant difference in the quality of life of the elderly in the UPT Social Services for the elderly and children under five in Binjai area between before and after giving group activity therapy to the control group with a p value of 0.317.There was a significant difference in the quality of life of the elderly in the UPT Social Services for the elderly and children under five in Binjai area between the intervention group and the control group with a p value of 0.043.